PERAN MEDIASI TRUST IN STORE PADA PENGARUH DIGITAL MARKETING DAN EWOM TERHADAP REPURCHASE INTENTION PADA KONSUMEN MARKETPLACES - Satria Pramudana, Agus; Santika, I Wayan; Rahanatha, Bayu; Arika, Diah (Buletin Studi Ekonomi; VOLUME.28.NO.02.TAHUN.2023, 2025)
This research aims to test and explain the role of trust in store in mediating the influence of digital marketing and electronic word of mouth on repurchase intention among consumers of online marketplaces in Denpasar City. The approach used is quantitative research with a sample of online marketplace consumers in Denpasar City. The data in this research was obtained by distributing questionnaires to a sample of online marketplace consumers in Denpasar City. Data analysis techniques use descriptive statistical analysis and inferential statistical analysis. The research results show that digital marketing has a positive and significant effect on repurchase intention. Electronic word of mouth has a positive and significant effect on repurchase intention. Digital marketing has a positive and significant effect on trust in store. Electronic word of mouth has a positive and significant effect on trust in store. Trust in store has a positive and significant effect on repurchase intention. Trust in store positively and significantly mediates the influence of digital marketing on repurchase intention. Trust in store positively and significantly mediates the influence of electronic word of mouth on repurchase intention among online marketplaces consumers in Denpasar City.